Mixed-Valence Single-Atom Catalyst Derived from Functionalized Graphene - Bakandritsos, Aristides; Kadam, Ravishankar G; Kumar, Pawan; Zoppellaro, Giorgio; Medved', Miroslav; Tuček, Jiří; Montini, Tiziano; Tomanec, Ondřej; Andrýsková, Pavlína; Drahoš, Bohuslav; Varma, Rajender S; Otyepka, Michal; et al. (Advanced materials (Deerfield Beach, Fla.), 2019)
Single-atom catalysts (SACs) aim at bridging the gap between homogeneous and heterogeneous catalysis. The challenge is the development of materials with ligands enabling coordination of metal atoms in different valence states, and preventing leaching or nanoparticle formation. Graphene functionalized with nitrile groups (cyanographene) is herein employed for the robust coordination of Cu(II) ions, which are partially reduced to Cu(I) due to graphene-induced charge transfer. Inspired by nature's selection of Cu(I) in enzymes for oxygen activation, this 2D mixed-valence SAC performs flawlessly in two O2 -mediated reactions: the oxidative coupling of amines and the oxidation of benzylic CH bonds toward high-value pharmaceutical synthons. High conversions (up to 98%), selectivities (up to 99%), and recyclability are attained with very low metal loadings in the reaction. The synergistic effect of Cu(II) and Cu(I) is the essential part in the reaction mechanism. The developed strategy opens the door to a broad portfolio of other SACs via their coordination to various functional groups of graphene, as demonstrated by successful entrapment of FeIII /FeII single atoms to carboxy-graphene.
Keywords: single-atom catalysis; amine coupling; CH oxidation; cooperative catalysis; graphene